Metaverso: El nuevo reto para los auditores. - Callejas , Luisa Fernanda; Roa Barón2, Nydia Esperanza (Fondo Editorial Universidad Antonio Nariño, 2024)
The metaverse is a digital environment that simulates spaces that imitate the real world allowing users to interact in it. Through the use of Virtual Reality (VR), allowing them to immerse themselves in digital environments using software that copies the world with the help of virtual reality headsets, allowing them to experience immersion in these new worlds; Augmented Reality (AR) modifies the vision of reality through inputs produced by an electronic device (Internet of Things - IoT) and Mixed Reality (MR) anchors virtual objects in the world in which they live and thus can interact.a united states english